Analisis Semiotika dan Hukum Humaniter Pada Dark Humor Debat Piers Vs Bassem Mengenai Konflik Hamas-Israel - Afryansyah; Septi Irianti; Mada Apriandi; Zaskia Zulaika Zuhir (Universitas Sriwijaya, 2025)
This research discusses the semiotics of dark humor thrown by Bassem regarding the Hamas-Israel conflict in the Piers vs Bassem debate. The purpose of this research is to find out the efficacy of dark humor in strengthening the argument and the meanings and thoughts contained in the dark humor delivered by Bassem Youssef. To get these results, descriptive analysis method is used with Charles Sanders Pierce's Semiotics theory. The data source of this research is the dark humor thrown by Bassem in the video 'Hamas-Israel war: Bassem vs Piers on Palestine's treatment' and managed to silence or produce a reaction from Piers Morgan. After the research, it was found that dark humor can strengthen some arguments because it reveals insights into social events and the impact of the war between Hamas and Israel expressed through dark humor. In addition, from some of his dark humor sentences, there are social phenomena that Bassem Youssef is trying to convey, including 1. Genocide, 2. ‘Human shield’ phenomenon, 3. Crimes against humanity committed by Israeli military groups before the events of October 7, 2023. The use of dark humor can reveal social events that are expected to be one from many ways to answer argument.